Analysis of Rab24 protein expression in mouse tissues - Farhad, Ahmed (My University, 2020)
Rab24 belongs to the Rab family of small GTPases that play important roles in intracellular vesicle formation, transportation, and fusion with target compartments. Almost 70 Rab proteins have been identified in humans so far and each Rab protein performs its specific functions at distinct stages of vesicular processes by interacting with multiple activators and targets. Rab24 is known to function in terminal stage of autophagic process i.e. in the maturation and clearance of autolysosomes. An important finding about Rab24 is the identification of a point mutation in Rab24 that changes glutamine to proline at position 38 leads to the loss of Purkinje neurons (highly metabolically active cells of cerebellar cortex) and causes ataxia in dogs. It is not known how Rab24 exerts its protective effect in these highly active neurons. Is this mechanism of neuronal protection related to the role of Rab24 in autophagy? Could this protection mechanism be exploited in the treatment of neurological as well as other disorders? In order to elucidate the functions of Rab24, an initial expression profiling of Rab24 protein in different tissues was performed in this study. Rab24 protein expression was analysed in brain, heart, liver, lungs, kidney, spleen, muscle, and fat of C57BL6 mice of different age groups, using Western blotting. In order to see which cell types in these tissues, express Rab24, immunohistochemistry was also performed. A gradual increase in expression of Rab24 was observed in most organs from 1-day-old to 9-month-old mice. Brain, lungs, kidneys, and spleen expressed high level of Rab24 protein as compared to other organs in all age groups. Furthermore, some additional bands of higher molecular weight were also observed with Rab24 protein bands (posttranslational modified bands of Rab24) in all organs except the brain, in 6- and 9-month-old mice.